CONVERSION TO ISLAM - Koovackal, George (Journal of Dharma, 2003)
Religious conversion has two important connotations, viz., theological and social. Theologically, it is an act of contrition asking forgiveness from God for the wrongs committed by the individual and community and the second signifies the change of one’s affiliation or membership from one religion to another. Islam, being a religio-political community, gives importance to both these aspects. Repentance or compunction of heart is considered something affecting one’s personal relationship with God while the conversion to Islam has a lot of social consequences. Every Muslim is keenly interested in spreading his faith. The early history of Islam shows that political leaders through their conquests have paved the way for the expansion of their religion. A lot of research has been carried out, and it continues even today, on the phenomenal growth of the Muslim community in the world and their results are not always in agreement with one another. Moreover, since the socio-religio-political situation differed from country to country we cannot postulate a uniform pattern or theory for the propagation of Islam. However, an attempt is made in this short paper to explore the Quranic concept of conversion and also to have a quick glance how Islam spread in a few countries. I shall, then, point out some factors that were responsible for the rapid expansion of Islam throughout the world.